An advanced clear-sky model for more accurate irradiance and illuminance predictions for arbitrarily oriented inclined surfaces. (June 2017) - Petržala, J.; Kómar, L.; Kocifaj, M.
Abstract: The article proposes a clear-sky physical model for the calculation of solar irradiances and illuminances. In contrast to other empirical models, ours takes into account the actual atmospheric pollution conditions, characterized by the optical parameters of atmospheric aerosols. Even if these optical parameters have not been measured directly, the model enables us to estimate their values from routinely measured solar radiation or daylight quantities at actinometric or daylight measurement stations and consequently to predict quantities not directly measured: irradiances and illuminances on arbitrary oriented or inclined surfaces. The software solution we have developed is demonstrated by a set of numerical experiments that are compared against the measurements. Highlights: An advanced clear-sky physical model of the solar irradiance is proposed. Irradiance on arbitrarily selected surface from bulk aerosol parameters is calculated. Estimation of aerosol parameters from measured diffuse and direct irradiances is shown. Calculation tool based on the model is presented for routine data processing.